A Dictionary of diplomacy and International affairs: English- French- Arabic = Mu'jam al al dibalumasiyyah wa al shu'un al dawliyyah - Samouhi Fawq el Adah (Maktabah Libanon, 1996)
ws.c.1-3/stoc6, c.1-2